Preparation and characteristics of solid base hydrotalcite - Son, Pham Anh; Canh, Kieu Thanh; Lan, Do Thi (Vietnam Journal of Chemistry, 2016)
In this report, we announce the fabrication of hydrotalcite compounds (HTs) with different molar ratios of Mg/Al by constant pH at low supersaturation method. The obtained compounds could serve as solid base catalysts. The crystal structure and phase composition were investigated by X-Ray Diffraction technique. The increase in Mg/Al molar ratio led to the expansion of the interlayer spacings of brucite-like layers in HTs because of the substitution of small ions (Al3+) by larger ions (Mg2+) in the octahedra of hydroxide layers. The elemental analysis proved the compatibility of experimental Mg/Al molar ratios and theoretical values. The presence of function groups was elucidated by FT-IR method. The results of thermo-analysis exhibited that the structure of HTs collapsed at temperatures higher than 400 oC due to the dissociation of HTs to MgO and Al2O3. The base site density determined by titration method was found to be directly related with Mg/Al molar ratio. The catalytic activity was tested on the glucose to fructose isomerization reaction. In all tested samples, HT5 gave the highest activity with fructose yield of 16.3%. Alongside HT1-HT5 chain, the catalytic activity increased versus Mg/Al molar ratio, as well as the density of base site. Keywords. Hydrotalcite, solid base catalyst, glucose, fructose, isomerization reaction.